Value Chain Model in Zakat Management at Makassar City National Amil Zakat Agency - Rauf, Deddy Ibrahim (Economics and Business Journal (ECBIS), 2022)
This research aims to determine the application of value chain model in zakat management at the Makassar City National Amil Zakat Agency. Population in this research is financial statements BAZNAS Makassar City in 2016 to 2018. Sample this research is data zakat conducted by BAZNAS Makassar City in 2016-2018. Data collection in research is by documentation, observation and interviews. The analysis technique used is descriptive method of value chain model analysis. The results showed that value chain model application can describe the activities carried out and increase the BAZNAS Makassar City value added. Primary activities consisting of zakat receipts, management functions application, zakat distribution, distribution and services. Furthermore secondary activities consist of administration, technology development, human resources management, and institutional facilities.